2015
DOI: 10.1007/s10616-014-9833-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and oxidative alterations after exposure of cultured human whole blood cells to lithium metaborate dehydrate

Abstract: Boron compounds have an ability of supporting antioxidant properties in human and animal tissues. Lithium metaborate dihydrate (LiBO 2-2H 2 O; LMD) is commonly used in nonlinear optic materials, cellular phones and pagers. But, there are limited data on the genotoxic and antioxidant effects of LMD in cultured human whole blood cells. The aim of this study was to evaluate for the genotoxicity and antioxidant/oxidant activity of LMD on human whole blood lymphocytes (n = 5). LMD was applied at various concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The obtained data showed that there was no significant increase in MN rates in erythrocytes exposed to COL as compared to control values. These findings are consistent with previous evaluations (Celikezen, Turkez, Togar, & Izgi, 2014;Celikezen et al, 2016). At the end of the study, it was determined that COL had no geno-toxic damage potential.…”
Section: Micronucleus In Zebrafish Erythrocytessupporting
confidence: 91%
See 1 more Smart Citation
“…The obtained data showed that there was no significant increase in MN rates in erythrocytes exposed to COL as compared to control values. These findings are consistent with previous evaluations (Celikezen, Turkez, Togar, & Izgi, 2014;Celikezen et al, 2016). At the end of the study, it was determined that COL had no geno-toxic damage potential.…”
Section: Micronucleus In Zebrafish Erythrocytessupporting
confidence: 91%
“…Alterations in enzyme activity and DNA damage are widely used as important biomarkers to reduce the geno-toxicity and oxidative stress of natural and / or man-made chemical materials (Celikezen, Toğar, Özgeriş, Izgi, & Türkez, 2016). Increased levels of MDA and MPO obtained at the highest dose of COL (20 mg/l) indicated the occurance of oxidative stress.…”
Section: Dna Damage Grade and Apoptosis Levelmentioning
confidence: 99%
“…Currently, more and more research on the therapeutic effect of the borax, mainly including anti-tumor effect and affecting the tumor growth, development and metastasis [26,27]. A great number of studies have concentrated on the application of borax for tumor prevention and illustrated a strong inverse correlation between borax and various types of cancer, including lung cancer, cervical cancer, prostate cancer and hepatocellular carcinoma (HCC) [2,8,9]. But, the underlying mechanisms of anti-tumor effect remain unidentified and borax administered altered the expression of miRNAs in HepG2 cells has been reported less.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it demonstrated that those alterations were ascribed to certain cellular toxicities and genetic defects by borax. In recent years, numerous studies have focused on the application of borax for various types of cancer prevention, including liver cancer, prostate cancer, cervical cancer, and lung cancer [2,8,9]. Our previous results revealed that HepG2 cell proliferation was inhibited following 24-h borax (4 mM) treatment and demonstrated borax-induced apoptotic in a concentration-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, certain cellular toxicities indicated that those alterations were ascribed to genetic defects caused by borax in humans (14). Notably, it has been recently identified that borax treatment enhanced the resistance of DNA to titanium dioxide-induced damage (15). Taken together, numerous studies have focused on the application of borax for tumor prevention and demonstrated a strong inverse correlation between borax and various types of cancer, including prostate cancer, lung cancer, cervical cancer and hepatocellular carcinoma (HCC) (615).…”
Section: Introductionmentioning
confidence: 99%